A study on the status of public libraries in Laguna - De Ramos, Maria Cristina S. (School of Library and Information Studies, University of the Philippines Diliman, 2018)
Libraries in the Philippines have been evaluated before but most of those studies were done decades ago and/or were limited to cities in the NCR. This study aims to ignite the need and want for a nationwide library evaluation in the Philippines by beginning with an evaluation of public libraries in the province of Laguna. The Standards for Philippine Libraries or SPL created by the Professional Regulation Commission (PRC) was used to evaluate the libraries included in this study.